The Hasapi of the Batak Toba from Sumatra Indonesia - Sinin, Aaliyawani E.; Hamdan, Sinin; Mohamad Said, Khairul Anwar; Duin, Ezra A. M.; Musib, Ahmad Fauzi (North Carolina State University, 2024)
The hasapi of the Batak Toba from Sumatra, Indonesia is a plucked bowl-lute chordophone. Hasapi is a fretless chordophone with two strings. The tuning for the hasapi used in this study is based on the transcription of the song ‘Horbo Paung’ played in F major by Sam Sitio. The tuning used for the 2nd string is C4 (Do for open string) followed by D4, E4, and F4 for 1st, 2nd, and 3rd finger, respectively. The 1st string was tuned to G4 (So for open string), followed by A4, B4, and C5 for 1st, 2nd, and 3rd finger, respectively. At higher notes (1st string) the spectra did not display many harmonics, i.e., less partials compared to the lower note (2nd string). Both strings showed a regular signal, whereas the highest note C5 (the highest fundamental frequency from the 1st string) showed an irregular pattern with no significant overtone frequency. The intensity of the partials in both strings displayed the reduction in amplitudes i.e. not proportional to increasing harmonic frequency. The timbre from Adobe Audition showed that the time frequency analysis (TFA) was in accordance with the Picoscope spectra. Only TFA from C5 showed irregular pattern with respect to the Picoscope output.